MPK3/MPK6-mediated phosphorylation of ERF72 positively regulates resistance to Botrytis cinerea through directly and indirectly activating the transcription of camalexin biosynthesis enzymes. (9th September 2021) - Li, Yihao; Liu, Kun; Tong, Ganlu; Xi, Chao; Liu, Jin; Zhao, Heping; Wang, Yingdian; Ren, Dongtao; Han, Shengcheng
Abstract: Ethylene response factor (ERF) Group VII members generally function in regulating plant growth and development, abiotic stress responses, and plant immunity in Arabidopsis; however, the details of the regulatory mechanism by which Group VII ERFs mediate plant immune responses remain elusive. Here, we characterized one such member, ERF72, as a positive regulator that mediates resistance to the necrotrophic pathogen Botrytis cinerea . Compared with the wild-type (WT), the erf72 mutant showed lower camalexin concentration and was more susceptible to B . cinerea, while complementation of ERF72 in erf72 rescued the susceptibility phenotype. Moreover, overexpression of ERF72 in the WT promoted camalexin biosynthesis and increased resistance to B . cinerea . We identified the camalexin-biosynthesis genes PAD3 and CYP71A13 and the transcription factor WRKY33 as target genes of ERF72. We also determined that MPK3 and MPK6 phosphorylated ERF72 at Ser151 and improved its transactivation activity, resulting in increased camalexin concentration and increased resistance to B . cinerea . Thus, ERF72 acts in plant immunity to coordinate camalexin biosynthesis both directly by regulating the expression of biosynthetic genes and indirectly by targeting WRKK33. Abstract : MPK3/6 phosphorylates ERF72 at Ser 151 to coordinate camalexin biosynthesis and pathogen resistance in Arabidopsis by activating PAD3 and CYP71A13 transcription and indirectly targeting WRKK33.